Ultrasound-detected pathologies cluster into groups with different clinical outcomes: data from 3000 community referrals for shoulder pain. Issue 1 (December 2017) - Tran, Gui; Hensor, Elizabeth; Ray, Aaron; Kingsbury, Sarah; O'Connor, Philip; Conaghan, Philip
Abstract Background Ultrasound is increasingly used to evaluate shoulder pain, but the benefits of this are unclear. In this study, we examined whether ultrasound-defined pathologies have implications for clinical outcomes. Methods We extracted reported pathologies from 3000 ultrasound scans of people with shoulder pain referred from primary care. In latent class analysis (LCA), we identified whether individual pathologies clustered in groups. Optimal group number was determined by the minimum Bayesian information criterion. A questionnaire was sent to all patients scanned over a 12-month period (n  = 2322). Data collected included demographics, treatments received, current pain and function. The relationship between pathology-defined groups and clinical outcomes was examined. Results LCA revealed four groups: (1) bursitis with limited inflammation elsewhere (n  = 1280), (2) bursitis with extensive inflammation (n  = 595), (3) rotator cuff tears (n  = 558) and (4) limited pathology (n  = 567). A total of 777 subjects (33%) completed questionnaires. The median (IQR) duration post-ultrasound scan was 25 (22–29) months. Subsequent injections were most common in groups 1 and 2 (groups 1–4 76%, 67%, 48% and 61%, respectively); surgery was most common in group 3 (groups 1–4 23%, 21%, 28% and 16%, respectively). Shoulder Pain and Disability Index scores were highest in group 3 (median 48 and 30, respectively) and lowest in group 4 (median 32 and 9, respectively). Patients in group 4 who had surgery reported poor outcomes. Conclusions In a community-based population, we identified clusters of pathologies on the basis of ultrasound. Our retrospective data suggest that these groups have different treatment pathways and outcomes. This requires replication in a prospective study to determine the value of a pathology-based classification in people with shoulder pain.